Comparison of (18)F-FDG PET/CT and PET/MRI in patients with multiple myeloma - Sachpekidis, Christos (Am J Nucl Med Mol Imaging, 2015)
PET/MRI represents a promising hybrid imaging modality with several potential clinical applications. Although PET/MRI seems highly attractive in the diagnostic approach of multiple myeloma (MM), its role has not yet been evaluated. The aims of this prospective study are to evaluate the feasibility of (18)F-FDG PET/MRI in detection of MM lesions, and to investigate the reproducibility of bone marrow lesions detection and quantitative data of (18)F-FDG uptake between the functional (PET) component of PET/CT and PET/MRI in MM patients. The study includes 30 MM patients. All patients initially underwent (18)F-FDG PET/CT (60 min p.i.), followed by PET/MRI (120 min p.i.). PET/CT and PET/MRI data were assessed and compared based on qualitative (lesion detection) and quantitative (SUV) evaluation. The hybrid PET/MRI system provided good image quality in all cases without artefacts. PET/MRI identified 65 of the 69 lesions, which were detectable with PET/CT (94.2%). Quantitative PET evaluations showed the following mean values in MM lesions: SUV(average)=5.5 and SUV(max)=7.9 for PET/CT; SUV(average)=3.9 and SUV(max)=5.8 for PET/MRI. Both SUV(average) and SUV(max) were significantly higher on PET/CT than on PET/MRI. Spearman correlation analysis demonstrated a strong correlation between both lesional SUV(average) (r=0.744) and lesional SUV(max) (r=0.855) values derived from PET/CT and PET/MRI. Regarding detection of myeloma skeletal lesions, PET/MRI exhibited equivalent performance to PET/CT. In terms of tracer uptake quantitation, a significant correlation between the two techniques was demonstrated, despite the statistically significant differences in lesional SUVs between PET/CT and PET/MRI.